2015
DOI: 10.1186/s12864-015-2235-4
|View full text |Cite|
|
Sign up to set email alerts
|

Fusion transcript loci share many genomic features with non-fusion loci

Abstract: BackgroundFusion transcripts are found in many tissues and have the potential to create novel functional products. Here, we investigate the genomic sequences around fusion junctions to better understand the transcriptional mechanisms mediating fusion transcription/splicing. We analyzed data from prostate (cancer) cells as previous studies have shown extensively that these cells readily undergo fusion transcription.ResultsWe used the FusionMap program to identify high-confidence fusion transcripts from RNAseq d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Furthermore, the expression and tissue specificity of the fusion transcript correlated with expression patterns of the upstream parent gene ( 1 ). In accord, a more recent study of transcription read-through fusions in prostate cancer demonstrated that fusion transcript expression is similar to parental expression, and that fusion transcript levels respond similarly to androgen and anti-androgen treatment ( 114 ). By contrast, a study of cis -spliced fusions in prostate cancer found that only half of the fusions were significantly expressed relative to the parent genes ( 8 ).…”
Section: Data-intensive Computational Studies Of Gene Fusion Functionmentioning
confidence: 96%
“…Furthermore, the expression and tissue specificity of the fusion transcript correlated with expression patterns of the upstream parent gene ( 1 ). In accord, a more recent study of transcription read-through fusions in prostate cancer demonstrated that fusion transcript expression is similar to parental expression, and that fusion transcript levels respond similarly to androgen and anti-androgen treatment ( 114 ). By contrast, a study of cis -spliced fusions in prostate cancer found that only half of the fusions were significantly expressed relative to the parent genes ( 8 ).…”
Section: Data-intensive Computational Studies Of Gene Fusion Functionmentioning
confidence: 96%
“…In addition, each of the six samples also expressed an isoform of P2RY8-CRLF2 which joined the first exon of P2RY8 to the 5' UTR of CRLF2, and resulted in an inframe transcript. This alternate fusion also featured the typical GT/AG donor/acceptor motif which exists at the majority of fusion junctions (Lai et al, 2015). The presence of the alternate breakpoints in the samples was confirmed using PCR and Sanger sequencing.…”
Section: Identification Of Novel Fusion Isoforms In P2ry8-crlf2mentioning
confidence: 66%
“…In addition, each of the six samples also expressed an isoform of P2RY8-CRLF2 that joined the first exon of P2RY8 to the 5′ UTR of CRLF2 and resulted in an in-frame transcript. This alternate fusion also featured the typical GT/AG donor/acceptor motif that exists at the majority of splice junctions [ 21 ]. The presence of the alternate fusion isoforms in the samples was confirmed using Reverse Transcription PCR and Sanger sequencing.…”
Section: Resultsmentioning
confidence: 99%